(untitled) (Journal of the College of Education for Women, 2019)
Ibn al-Haytham is the pioneer of optics, which is a science that had described optics circumstances. Optics or landscape science as it was known by the Arab and Muslim scientists at the time when is a science known as the conditions of sighters in their quantity and quality as the proximity and distance from the beholder , the different forms , conditions and what mediate between the beholder and the microscopes , to explain useful knowledge of what obscures the sight of the conditions of sighters and is used to measure the space Distant criminality and mirrors. Ibn al-Haitham wrote his famous book The Book of Mirrors and studied mistakes adopted the method of research and practical experience in expressing his views. Keyword: Ibn Al-Haytham , drugs, optics